(3OdGFd GdCMcGe aj TQM TQGFY GdESdGes - (3GdehShj GdbRhjfj, EHQGgje Hf eMeO HGbQ, (B1264 (3g`s ((3Ydj Hf egOj GdWgQGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3bhdg cJGH GdWgGQI GSe ddhVhA hGdZSd hGdJjee Ydi hLg dg JCKjQ aj GSJHGMI GdUdGI , GdWgGQI dZI MbjbI aj GdfXGaI hGdfRGgI eTJQcI HjfgeG (B... (3HGdfSHI Edi GdCNjQ ddYQa hTQYG (B...s
(3BNQgG (B:s
... (3heJi GQJaYJ aj GdCHfGA CSHGH GdJeGe hbdfG HdRhe GdbUQ aj Pdc GdebGe (B... (3GdJbUjQ eGde jJLGhR eMdg HEceGd GdbjGe Edi GdKGdKI hEdG HWdJ hCYGO bUQ ceG JQ aj GdQLhY Yf GdEbGeI agPG BNQ GdeLdO GdChd (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\70s
(3EjVGM Gdecfhf (B1\476s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis